Concept Paper on Teachers' Preparedness for Early Detection of Preschool Children's Disabilities - Zulkefli, Norazua binti; Tahar, Mohd Mokhtar (Angstrom Centre of Education, 2023)
The purpose of this study is to examine the level of readiness of teachers based on their knowledge, skills and attitudes towards screening techniques among pre-schoolers and identify types of screening conducted by the teachers. The study refers to several recent journals in the form of systematic analysis as studies supporting the issues to be debated in this concept paper. The findings show that teachers do not have sufficient knowledge and skills in screening of pupil of who are at risk of disabilities. This leads to an unhealthy attitude in conducting screening method. The findings also identify the types of screening performed by teachers through the checklist and test adapted from abroad. Ministry of Education (MOE) may take approaches and initiatives to provide courses for teachers on speech and occupational in performing screening. Furthermore, MOE can also place therapist and interventionist officials in schools as one of the steps to realize the initial screening of disability based in the Zero Reject Policy. Positive acceptance from parents affects teachers in implementing the screening of pupil of who are at risk of disabilities. At the same time, reducing the risk of disability and increasing the preschooler’s readiness going to school later.